Erratum. (December 2014) - Unknown
The publisher would like to apologise for an error made in the journal of Simulation: Transactions of The Society for Modeling and Simulation International . The author's name, S. Daicz, in reference 26; 'A Component-based Simulator for MIPS32 Processors', was incorrectly spelt. The reference should have read as follows: [1] A Component-based Simulator for MIPS32 Processors [1] [26] Wainer, G., S. Daicz and A. Troccoli. 2001. Experiences in modelng and simulation of computer architectures in DEVS. Simulation Transactions, 18(4): 179–202. DOI:10.1177/0037549709346279